1999
DOI: 10.1093/ajcn/69.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of small-intestinal fat and carbohydrate infusions on appetite and food intake in obese and nonobese men

Abstract: To determine whether the satiating effects of nutrients in the small intestine are lower in obese than in nonobese people, 9 healthy, obese men [age: 18-33 y; body mass index (BMI; in kg/m2) 30.4-40.8] and 11 healthy, nonobese men (age: 18-33 y; BMI: 19.1-26.4) received an intraduodenal infusion of saline (control), lipid ( 11.97 kJ/min, or 2.86 kcal/min), or glucose (11.97 kJ/min) for 120 min on separate days. Fullness, hunger, and nausea were assessed by visual analogue scales. After the infusions, a meal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
3
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 49 publications
4
50
3
1
Order By: Relevance
“…Thirteen healthy males were included in the study; the number of subjects was based on power calculations derived from a previous study (6). We calculated that with 13 subjects we would observe a 10% decrease in energy intake at ␣ ϭ 0.05, with a power of 80%.…”
Section: Subjectsmentioning
confidence: 99%
“…Thirteen healthy males were included in the study; the number of subjects was based on power calculations derived from a previous study (6). We calculated that with 13 subjects we would observe a 10% decrease in energy intake at ␣ ϭ 0.05, with a power of 80%.…”
Section: Subjectsmentioning
confidence: 99%
“…Intraduodenal fructose, but not glucose, infusions in humans resulted in decreases in energy intake compared with saline infusions (10,11). Intraileal glucose infusions have been found to suppress energy intake to a greater extent than intraduodenal infusions in rats (12).…”
Section: Discussionmentioning
confidence: 98%
“…The rats were then divided into 3 groups to ensure an equal average body weight and SEM per group (GLU = 384 6 11.7 g, FRU = 394 6 12.9 g, and SAL = 392 6 9.8 g). Each group received either an equal kilocalorie load of GLU or FRU (11.4 kcal; Sigma-Aldrich), or SAL at a rate of 0.2 mL/h for 7 h at the beginning of the daily dark period for 5 d. An isotonic saline solution has been used previously as a control solution in human (10,11) and nonhuman animal (12,13) intestinal infusion studies. The parameters were chosen on the basis of previous research that showed a reduction in energy intake over a multiday infusion of an equal caloric load and duration of infusion of glucose and other nutrients, which we have used previously (8) and that have been used by others (13).…”
Section: Methodsmentioning
confidence: 99%
“…Intragastric and intraintestinal infusions of either linoleic or oleic acid have been demonstrated to reduce food intake and body weight in humans, rats and other animal models (4,6,7,8). Numerous studies have indicated a role for CCK, signaling via vagal afferent neurons in the gut and setting in motion a robust gut-satiety cascade.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature suggests that some of these meal-related signals originate in the gastrointestinal tract and serve to terminate ingestion (5,11). Previously, studies have shown that intraintestinal infusions of long-chain fatty acids significantly reduced voluntary food intake (4,16): the mechanisms that control this response are complex, but likely involve gut-initiated satiety signals (9). Numerous gastrointestinal peptide hormones are released during and immediately after food intake, including cholecystokinin, peptide YY, glucagon-like peptide 1, and oxyntomodulin, which act either distally, signaling satiety and suppressing food intake via receptors located in the central nervous system, or proximally, by slowing gastric emptying (22,27).…”
Section: Introductionmentioning
confidence: 99%